Cattle Marketing System in Bena-Tsemay District of South Omo, South-Western Ethiopia - Adane, Zelalem; Hidosa, Denbela (Research on World Agricultural Economy, 2022)
The absence of information on cattle marketing systems is a major challenge for cattle producers and policymakers in Ethiopia. Therefore, this study was conducted in the Bena-Tsemay district with the aim of assessing the cattle marketing system. The household survey involved the interviewing of 150 households of eight Kebeles, which were purposefully selected from the three cattle production systems. The qualitative parameters, such as cattle market infrastructures, cattle transportation facilities, cattle market information, cattle marketing channels, cattle market actors, and the extent of extension service in the cattle marketing system, were analyzed using non-parametric methods, while the means of the quantitative parameters, such as cattle price and a number of cattle supplies, were analyzed using a one-way ANOVA of SPSS, version 20. The results revealed that the majority (73.2%) of the cattle keepers in three production systems sold their cattle; while very few (24.8%) did not. Approximately 58.33% of respondents said they bought and sold cattle at the local market using eyeball estimation, while only 12.2% used a bartering system. The majority of cattle keepers (69.30%) have access to cattle market information, while a few of them (30.7%) do not have access to cattle market information. The prices of selling and purchasing cattle were determined via peaceful negotiations between cattle sellers and traders (66.7%), while a small percentage (33.3%) was determined only by the cattle seller’s decision. The lack of cattle market and transportation facilities, the lack of cattle market price promotion centers, the lack of credit services, and the lack of capacity buildings were the major cattle marketing constraints. Thus, based on the results, the authors concluded that capacity-building and development efforts should be designed for cattle market transport facilities, legal cattle market promotion centers, credit services, and cattle feeding and health improvement strategies. ER